First Report of a Fish in the Diet of Brown Shrike Lanius cristatus Linnaeus, 1758, from Punchakari-Vellayani Wetlands, Thiruvananthapuram, Kerala, India - Susanth, C.; Gokul, R. S. (Journal of the Bombay Natural History Society (JBNHS), 2022)
No Abstract.